Structure identification of α-glucans from Dictyophora echinovolvata by methylation and 1D/2D NMR spectroscopy. (15th January 2019) - Shi, Xiao-dan; Li, Ou-ye; Yin, Jun-yi; Nie, Shao-ping
Highlights: Polysaccharides with different physicochemical properties were characterized. They were linear α-(1 → 4)-glucans with α-Glc p units linked at C-6 of the backbone. Conformational parameters ([ η ] & R h ) decreased with molecular weights decreasing. Abstract: Dictyophora echinovolvata is a kind of edible mushroom in the Dictyophora genus, of which polysaccharide is an important chemical substance. Herein, three polysaccharide fractions (DEP-4P, DEP-6P and DEP-8P) were prepared from water extract of D. echinovolvata using gradient ethanol precipitation method. Their chemical structures were analyzed by methylation analysis and 1D/2D NMR spectroscopy. Molecular weights were determined by multi-angle laser light scattering combined with size-exclusion chromatography (HPSEC-MALLS). HPSEC data showed that DEP-4P had the highest values of molecular weight, intrinsic viscosity and hydrodynamic radius. DEP-6P and DEP-8P had lower molecular weights, which contributed to their easily distinguished 1D and 2D NMR spectra. Methylation and NMR analysis suggested that the three fractions were linear α-(1 → 4)-glucans with α-Glc p residues linked to the backbone at C -6. Differences among the three fractions were the molar ratios of the identified glycosidic bonds. Repeating units of polysaccharides from D. echinovolvata were proposed as follows: